Heparan Sulfate Organizes Neuronal Synapses through Neurexin Partnerships - Zhang, Peng; Lu, Hong; Peixoto, Rui T; Pines, Mary K; Ge, Yuan; Oku, Shinichiro; Siddiqui, Tabrez J; Xie, Yicheng; Wu, Wenlan; Archer-Hartmann, Stephanie; Yoshida, Keitaro; Tanaka, Kenji F; et al. (Cell, 2018)
Synapses are fundamental units of communication in the brain. The prototypical synapse-organizing complex neurexin-neuroligin mediates synapse development and function and is central to a shared genetic risk pathway in autism and schizophrenia. Neurexin's role in synapse development is thought to be mediated purely by its protein domains, but we reveal a requirement for a rare glycan modification. Mice lacking heparan sulfate (HS) on neurexin-1 show reduced survival, as well as structural and functional deficits at central synapses. HS directly binds postsynaptic partners neuroligins and LRRTMs, revealing a dual binding mode involving intrinsic glycan and protein domains for canonical synapse-organizing complexes. Neurexin HS chains also bind novel ligands, potentially expanding the neurexin interactome to hundreds of HS-binding proteins. Because HS structure is heterogeneous, our findings indicate an additional dimension to neurexin diversity, provide a molecular basis for fine-tuning synaptic function, and open therapeutic directions targeting glycan-binding motifs critical for brain development.